Cooperation and Discord in U.S.-Soviet Arms Control - Weber, Steve, 1961- (Book collections on Project MUSE., 2014)
If international cooperation was difficult to achieve and to sustain during the Cold War, why then were two rival superpowers able to cooperate in placing limits on their central strategic weapons systems? Extending an empirical approach to game theory--particularly that developed by Robert Axelrod--Steve Weber argues that although nations employ many different types of strategies broadly consistent with game theory's ""tit for tat, "" only strategies based on an ideal type of ""enhanced contingent restraint"" promoted cooperation in U.S.-Soviet arms control. As a theoretical analysis of the